Rare-Earth Pretreatment Improves Performance of Reactive Dye Argazol Navy Blue on Banana-Fiber Fabric - Ao Du; Yongjie Zheng; Wenqi Jiang; Jie Liu (Molecules)
At present, the use of conventional reactive dyes on banana-fiber fabric leads to the problem of excessive salt consumption, which is not conducive to environmental protection. In this experimental study, rare-earth-pretreated banana-fiber fabric was dyed with the reactive dye Argazol Navy Blue. The rare-earth pretreatment was carried out to reduce the level of salt consumption, improve dyeing and fixation rates, and reduce the treatment burden of printing and dyeing wastewater. Dye uptake and fixation rates were used as indicators. Single-change factors were assessed by analyzing different amounts of rare earth, sodium carbonate, and sodium chloride, as well as different fixation times and temperatures, so that the effects of the dye additive on the dyed banana-fiber fabric could be investigated. After appropriate ranges were determined for single-change factors, an orthogonal experiment was carried out to establish optimal parameters for the process of dyeing rare-earth-pretreated banana-fiber fabric with Argazol Navy Blue. These parameters were as follows: the required amount of rare earth was 0.40% (o.w.f.); the amount of dye was 2% (o.w.f.); the amount of sodium chloride was 15 g/L; the amount of sodium carbonate was 9 g/L; the fixing temperature was 75 °C; and the fixing time was 45 min. These optimized process parameters were then used to dye the banana-fiber fabric as a whole. Our results showed that the dye uptake and fixation rates for rare-earth-pretreated banana-fiber fabric dyed with navy-blue dye reached 56.85% and 45.32%, respectively. Finally, the effect of rare-earth pretreatment on dyeing performance was analyzed using FT-IR, SEM, and EDS.